Implementasi Jaringan Fiber Optik Dalam Integrasi Studio Produksi Media di STMM Yogyakarta - Wahyudin, Ade; Prasetyo, Lilik Jatmiko; Astuti, Aprilina Dwi (Jurnal Ilmiah Multimedia dan Komunikasi, 2025)
This study aims to evaluate the implementation of fiber optic networks to improve integration and transmission efficiency in the media production studios at STMM Yogyakarta. In broadcasting environments, network stability and high-speed data transmission are essential to ensure seamless delivery of high-quality audio-visual content. Optical fiber, known for its superior bandwidth and low latency, presents a suitable technological solution. Through experimental testing using Wireshark software, this research measures key network parameters—throughput, delay, packet loss, and jitter—in two studio environments. The results reveal that Studio 2 demonstrates optimal performance with a maximum throughput of 11,286.42 Kbps, an average delay of 2.98 ms, 0% packet loss, and minimal jitter. In contrast, Studio 1 exhibits lower throughput, higher delay and jitter, and packet loss of up to 5.5%, indicating the need for technical improvement. The study highlights a research gap regarding fiber optic implementation in educational broadcast studios and offers practical recommendations such as network configuration optimization, equipment upgrades, and Quality of Service (QoS) implementation. These findings are expected to enhance practicum quality and align the learning environment more closely with industry standards.